Debunking leftward progress. (26th December 2018) - Huemer, Michael
Abstract: In earlier work, I argued that observed changes in moral values over human history are best explained as cognitive progress: societies tend over the long term to move closer to the objective moral truth. It is also true that, in recent decades, liberal democracies have moved strongly in the direction of greater government regulation and wealth redistribution. Does this mean that extensive regulation and redistribution are objectively good? I argue that the answer is no; these recent trends are importantly different from earlier examples of moral progress in ways that enable them to be satisfyingly explained without adverting to objective moral correctness.